The Emergence of Personal Myth in the Essays of Dalia Staponkutė - Vedrickaitė, Imelda (Colloquia, 2015)
Within the rapidly expanding field of emigration and migration literature, Dalia Staponkutė’s essay collections are notable for their intellectualism and probing anthropological gaze. They have drawn the attention of literary critics for their intense and intentional hybridity, positive understanding of émigré experience, grounding of the concept of identity in the author’s native language. The author of this article offers a broader study of the resonances of Staponkutė’s subject, of the wanderer’s conceptualization of spatial and temporal metaphors. The essay narrator’s focus slides from the Lithuania-Cyprus, NorthSouth geographic and cultural landscape to the temporal zone of the wanderer’s introspection and self-invention. Staponkutė articulates the state of personal freedom, particularly the philosophizing observer’s freedom, through the spatial images of the island and of the margins of empire. Rather than inertly holding onto inherited or learned ideas about identity or human roles (nationality, language, parenthood, the intellectual’s responsibility toward her homeland), Staponkutė tests freedom of thought and behavior against personal life experience. In order to survive in a globalizing, leveling world, she arranges a personal myth from her experience as mother, philosopher, traveler, and communicator while resisting traditional attitudes and stereotypical ideas about these roles. The biographical in Staponkutė’s essays embodies Alphonso Lingis’ thoughts about personal myth – the need to describe the world as one finds it, to create an individual means of transforming one’s surroundings into an organized semantic structure. The intensity of lived time, the attempt to be fully there, where one is (i.e., to live and create freely), and the perpetually present horizon of death both allow and force Staponkutė to retreat from the field of the traditional tension between self and other. In it, the wanderer qualitatively renews his aesthetic relationship with the world, the direction of his wanderings toward the homeland apparently restoring a lost romantic dimension, and love of, servitude.